European energy security reimagined: Mapping the risks, challenges and opportunities of changing energy geographies - Ellen Scholl; Kirsten Westphal (Stiftung Wissenschaft und Politik (SWP), 2017)
Following the Paris Agreement, the energy landscape is changing more than ever. While these changes bring opportunity, they also come with risks, requiring traditional concepts of energy security to be reconsidered. These changes in the energy landscape are mirrored by shifting political balances as the world becomes increasingly multipolar, raising questions of which rules will govern energy systems, trade, markets and investment. As geopolitical turmoil comes closer to the EU's borders, energy systems are becoming increasingly cross-border and regional in nature, intertwining interest in energy security. Cross-border initiatives in energy are proliferating across Eurasia, driven in part by the rise of China, with the potential to create new energy regions, corridors and geographies. These developments can lead to new geographies along infrastructure lines and could result in competitive regionalism and regulatory fault lines. This paper reflects an initial step to identify potential risks emerging in this new energy landscape and assess the ability of existing institutions and tools of governance to address them. The study aims to describe the risk landscape and governance shortcomings and identify actions the EU can take to both improve its existing external energy governance and empower existing institutions to address these risks. Ultimately, for the EU and Germany, the challenge will be to turn the potential risks of connectivity into opportunities and to help establish a level playing field that ensures competitiveness through common rules. (SWP Research Paper)
Keywords: 320